COMMUNICATION ABILITYDALAM PEMECAHAN MASALAH PERUBAHAN IKLIM SESUAI PERSPEKTIFGENDER - Al Haeriyah Sucia (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The purpose of this study is to observe the ability of verbal communication in solving the problem of climate change with the traditional architecture of Sasak Ende. The method used in this research is description with purposive sampling technic. This study viewed from the gender differences. The research subjects consist of 2 villagers of Sasak Ende village. Technique of data analysis through two stages; (1) data presentation, and (2) data conclusion. The results of this research are The results showed that the ability of male verbal communication in solving environmental problems better than women.